Neurosarcoidosis As a Rare Differential Diagnosis for Single Or Multiple Lesions of the Nervous System. (2nd September 2020) - Blume, Christian; Tuleta, Izabela; Nolte, Kay; Eichhorn, Klaus W.; Jakob, Mark; Clusmann, Hans; Send, Thorsten
Abstract: Objective: Sarcoidosis is a multisystemic granulomatous disease of unknown cause which affects the lung or bilateral hilar lymphadenopathy in over 90% of the cases. Neurosarcoidosis (NS) is rare and accounts for approximately 5 – 15% of the cases. Involvement of all parts of the central and peripheral nervous system is possible with various clinical symptoms, e. g. seizures, hydrocephalus, optic/facial nerve palsy or hearing loss. Methods: We screened the neuropathological data bases and the medical records of two neurosurgical university hospitals for cases of NS. All these cases had been verified by surgical biopsy. We retrospectively evaluated the patient's records with special regard to the histopathology reports and specific clinical symptoms. Results: We identified 9 cases of NS between 1994 and 2014 (3 female, 6 male patients). The average age at the time of diagnosis of NS was 41, 4 years. Various clinical symptoms like hydrocephalus ( n  = 3), seizures ( n  = 1), meningitis ( n  = 1), optical nerve involvment with vision disorder ( n  = 1), myelitis with paraplegia ( n  = 1), mastoiditis with hearing loss ( n  = 1), back pain syndrome ( n  = 2) were present. 7 patients were treated with corticosteroids, 1 patient with cyclophosphamide and 1 with a combination of corticosteroids and methotrexate. Conclusion: NS is a rare but potentially life-threatening disease. It is difficult to distinguish sarcoidosis from other granulomatous diseases, infectious diseases like tuberculosis, multiple sclerosis or neoplasm. For a definite diagnosis, a neurosurgical biopsy with histological evidence of noncaseating epithelioid cell granulomas is required, followed by multidisciplinary treatment.